Terapi Kompres Dingin Untuk Menurunkan Skala Nyeri Akut Pasien Fraktur : Systematic Review - Trias Eka Nurlela; Henny Suzana Mediani; Urip Rahayu (Tribhuwana Tunggadewi University, 2023)
The unpleasant experience of post-fracture patient pain can affect hemodynamics and impaired mobilization. One of the non-pharmacological therapies, cold compress therapy has proven to be effective for treating acute pain in fracture patients. This review is to explore and evaluate the association with cold compress therapy in the management of acute pain in fracture patients and the outcomes provided for patients with various types of fractures. A systematic review was carried out using three electronic databases, namely Google Schoolar, PubMed and Journal of Islamic Nursing using key words in the search for articles determined using PICO. P: Patients with fractures, I: acute fracture pain, C: the effectiveness of cold compresses O: lowering the pain scale. Quasi-Experimental Articles published between 2013-2019 in English and Indonesian. This review looks at various types of fractures which assesses the effect of cold compress therapy in reducing the acute pain scale in fracture patients. Based on the search found 378 articles. Obtained 7 Quasi Experimental articles (165 participants) were identified and assessed for pain. Cold compress therapy is generally given with companion intervention starting from 10-15 minutes, with a temperature of 5 -10˚C using cold water (could pack) is effective for reducing pain and edema. Cold compress therapy is an easy and simple therapy that can be used as a companion to pharmacological therapy and has proven effective for fracture patients. We recommend using this therapy for fracture patients from the first 4 hours post-fracture or 7-8 hours post-surgery to reduce pain from 4-5 to a 3-2 scale.